2019
DOI: 10.1177/1533317519886218
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Living With Primary Progressive Aphasia: A Scoping Review of Qualitative Studies

Abstract: Introduction: Understanding the experiences of people who live with primary progressive aphasia (PPA) can inform the development of appropriate speech-language pathology services for this population. This review aimed to summarize the qualitative research on the experience of living with PPA from the perspective of the individuals with the disorder and their families. Methods: A scoping review was conducted. Results: Eight studies met the inclusion criteria. Themes in the 3 investigations that focused on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In contrast to PNFA and LPA, the impact of social communication disturbances in SD was evident both in terms of patient functional impairment and level of carer burden. This finding resonates strongly with a recent qualitative review of the lived experience in PPA in which carers of SD reported higher levels of perceived burden, which were largely driven by behavioural changes and rigidity in this syndrome [ 57 ]. Reduced conversational effectiveness in SD due to hallmark features of anomia and circumlocutions may be perceived by carers as topic derailment or oppositional behaviour (see also [ 19 ]).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast to PNFA and LPA, the impact of social communication disturbances in SD was evident both in terms of patient functional impairment and level of carer burden. This finding resonates strongly with a recent qualitative review of the lived experience in PPA in which carers of SD reported higher levels of perceived burden, which were largely driven by behavioural changes and rigidity in this syndrome [ 57 ]. Reduced conversational effectiveness in SD due to hallmark features of anomia and circumlocutions may be perceived by carers as topic derailment or oppositional behaviour (see also [ 19 ]).…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, while social communication difficulties impinge negatively on everyday functional activities in these patients, they do not appear to be viewed as burdensome by carers and may reflect their relatively preserved capacity to connect socially in certain domains. The experience of PPA has been shown to vary widely depending on subtype and patient/carer perspective, whereby individuals with PPA tend to focus on language decline while family members concentrate their efforts on adapting to and managing socioemotional and behavioural changes [ 57 ]. When viewed in this light, the types of communication dysfunction assessed by the LCQ are likely to be anticipated by carers as part of the typical disease trajectory in PNFA and LPA and perceived as more manageable.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of diagnosis, patients and their families often inquire about what to expect in terms of the progression of symptoms and nature of upcoming deficits, which will have a significant impact on their daily life and functional communication. Few studies have explored the challenges faced by patients and caregivers [14][15][16]. Greater knowledge of the evolution of the three PPA variants would allow better counseling and help orient better clinical approaches for this population as the disease progresses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, having consistent peer support helps to “normalise” daily challenges. It has been suggested that self-help groups may be beneficial in maintaining the group intervention benefits and they are recommended even in the absence of professional input [ 103 ].…”
Section: Support Groups and Educational Programmesmentioning
confidence: 99%